2021
DOI: 10.1080/16549716.2021.1927507
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics of stroke and its rehabilitation in Northern Tanzania

Abstract: Background Stroke causes great suffering and severe disability worldwide, and rehabilitation following a stroke seeks to restore lost functions. The extent to which stroke patients get access to rehabilitation in Tanzania is not well estimated, and drawing a current picture of the rehabilitation services for these persons is the first step in developing a more effective rehabilitation model in the country. Objective The objective of this study was to establish the chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…Furthermore, occupational therapists and speech therapists are nearly absent across Zambia, and none are employed at our hospital so these services are unavailable to patients hospitalized at our facility. Similar findings have been reported from other hospitals in the region, including a study at Kilimanjaro Christian Medical Center Hospital, the largest and highest volume healthcare facility in Tanzania, where only 47% of adults hospitalized with stroke received access to rehabilitation during their hospitalization, and speech therapy was entirely unavailable 5 …”
Section: Stroke Rehabilitation From the Zambian Perspectivesupporting
confidence: 85%
See 1 more Smart Citation
“…Furthermore, occupational therapists and speech therapists are nearly absent across Zambia, and none are employed at our hospital so these services are unavailable to patients hospitalized at our facility. Similar findings have been reported from other hospitals in the region, including a study at Kilimanjaro Christian Medical Center Hospital, the largest and highest volume healthcare facility in Tanzania, where only 47% of adults hospitalized with stroke received access to rehabilitation during their hospitalization, and speech therapy was entirely unavailable 5 …”
Section: Stroke Rehabilitation From the Zambian Perspectivesupporting
confidence: 85%
“…Similar findings have been reported from other hospitals in the region, including a study at Kilimanjaro Christian Medical Center Hospital, the largest and highest volume healthcare facility in Tanzania, where only 47% of adults hospitalized with stroke received access to rehabilitation during their hospitalization, and speech therapy was entirely unavailable. 5 After discharge, the vast majority of Zambian patients return directly home into the care of a family member who serves as an informal caregiver. Postdischarge inpatient rehabilitation facilities are not available in the public sector, and in-home nursing and rehabilitation services do not exist.…”
Section: Stroke Rehabilitation From the Zambian Perspectivementioning
confidence: 99%
“…There was a predominance of ischemic stroke in the patients, being the first episode, corroborating with a study among poststroke people, in which 63.6% had ischemic stroke and 80.5% had the first episode. 11 A study carried out in Sweden 12 with 72.5% of the patients who had stroke being carriers of systemic arterial hypertension. Similarly, the present study identified the same modifiable risk factor in predominance.…”
Section: Discussionmentioning
confidence: 99%